Statistical process control - Oakland, John S. (Burlington, MA : Butterworth-Heinemann, 2008)
Statistical Process Control (SPC) is a tool that measures and achieves quality control, providing managers from a wide range of industries with the ability to take appropriate actions for business success. Offering a complete instructional guide to SPC for professional quality managers and students alike, all the latest tools, techniques and philosophies behind process management and improvement are supported by the author's extensive consulting work with thousands of organisations worldwide. Fully updated to include real-life case studies, new research based on actual client work from an array of industries, a new chapter on process capability, and integration with the latest computer methods and Minitab software, the book also retains its valued textbook quality through clear learning objectives and end of chapter discussion questions. It will serve as a textbook for both student and practicing engineers, scientists, technologists and managers and for anyone wishing to understand or implement modern statistical process control techniques. The complete instructional guide to SPC, with links to Six Sigma/Lean approaches, helping managers to communicate the philosophy of process management and improvement as a key to business success Written by a leading guru on total quality management, this fully modernised new edition includes real-life case studies, new research based on actual client work from an array of industries, and a new chapter on process capability An ideal textbook with clear learning objectives and end of chapter discussion questions, a non-mathematical and practical style, along with the integration of the latest computer methods and Minitab software.
Part 1: Process Understanding and Management: Quality, Processes and Control; Understanding and managing processes; Process data collection and presentation. Part 2: Process Variability: Variation and its management; Variables and process variation. Part 3: Process Control: Process control using variables; Other types of control charts for variables; Process control by attributes; Cumulative sum (cusum) charts. Part 4: Process Capability: Process capability for variables and its measurement; Process capability for attributes -- sampling. Part 5: Process Improvement: Process problem solving and improvement; Managing out-of-control processes; Designing the statistical process control system; Six-sigma process quality; The implementation of statistical process control. Appendices.
Διαθέσιμο και σε ηλεκτρονικό βιβλίο, τρόπος πρόσβασης μέσω διαδικτύου.
Includes bibliographical references and index.
Keywords: Process control -- Statistical methods; Electronic books